Centre-Periphery and Specialization in the E. U.: An Analysis From a New Economic Geography Perspective - Helen Caraveli; John Darzentas (European Regional Science Association (ERSA), 2006)
This paper attempts an assessment of a number of basic statistical indicators of EU regions and countries from a New Economic Geography (NEG) perspective. After a brief overview of the underlying theoretical framework, two important hypotheses of NEG's theoretical models are examined for the case of EU regions: (a) the existence of a center-periphery pattern, with the use of indicators measuring the "home market effect"; (b) the existence of Marshall-type "economies of localization", as well as of "dynamic external economies", on the basis of "knowledge-intensive" and "human capital" indicators. This analysis takes place on a regional scale. An assessment of the evolution of specialization in EU countries is also undertaken with the use of an index of "regional specialization". The analysis provides clear indications that, the deepening of European integration led to both phenomena described by NEG models: (a) the strengthening of two types of concentrations – "the enlargement of the home market" and "local external economies" - in the traditional industrial centres of the EU; (b) an increase in the degree of specialization of its member-states. Policy implications point to the strengthening of factors that could lead to the development of new dynamic centres in peripheral EU regions.
Keywords: 330